Pharmaceutical compositions and methods for enhancing solubility of poorly soluble active pharmaceutical ingredients
By using poloxamer with a melting point of 20°C or higher to form a pharmaceutical dosage form in the selective laser sintering process, the problem of insufficient application of poloxamer in the SLS method is solved, and the preparation of amorphous solid dispersion is realized and Improvements in API release.
Patent Information
- Application Number
- CN202380051695.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-06
- Filing Date
- 2023-07-03
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, poloxamer has fewer applications in selective laser sintering (SLS) methods, and the suitability of different poloxamer levels is unknown, making it difficult to form pharmaceutical dosage forms with improved performance.
Using poloxamer with a melting point of 20°C or higher, a drug dosage form is formed through a selective laser sintering process, and combined with the use of low process temperature, the preparation of amorphous solid dispersion is achieved.
The successful manufacturing of amorphous solid dispersions under low temperature conditions has been achieved, which improves the release speed and bioavailability of APIs, reduces the energy required for printing and expands the scope of application of SLS printers.
Smart Images

Figure BDA0005227029880000041 
Figure BDA0005227029880000051 
Figure BDA0005227029880000052
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to the use of poloxamers in additive manufacturing technologies and techniques. More specifically, the present disclosure relates to the use of poloxamers in the additive manufacturing of objects, particularly pharmaceutical dosage forms, in a selective laser sintering (SLS) process. Background Art
[0002] Poloxamers are nonionic poly(ethylene oxide) (PEO)-poly(propylene oxide) (PPO) copolymers. They have many functions as surfactants, emulsifiers, solubilizers or dispersants in pharmaceutical formulations. All poloxamers have similar chemical structures, but have hydrophilic PEO blocks (A) and hydrophobic PPO blocks (b) with different molecular weights and compositions (Bodratti AM, Alexandridis P. Formulation of poloxamers for drug delivery. Journal of functional biomaterials. 2018; 9(1): 11).
[0003] Poloxamer can be used to improve the oral bioavailability of low solubility compounds by heating solid dispersions. The preparation of amorphous solid dispersions with poloxamer is usually quite complicated. One strategy is to dissolve the polymer and the API and perform a freeze-drying step to produce the final ASD (Song CK, Yoon IS, Kim DD.Poloxamer-based solid dispersions for oral delivery of docetaxel:Differential effects of F68and PSS on oral docetaxel bioavailability.International Journal ofPharmaceutics.2016;507(1):102-8.). Many ternary systems are also described in the literature, in which small amounts of poloxamer are added to polymer carriers to enhance the bioavailability of low-solubility compounds (Vasconcelos T, Prezotti F, Araújo F, Lopes C, Loureiro A, Marques S, et al., Third-generation solid dispersion combining Soluplus and poloxamer enhances the oral bioavailability of resveratrol. International Journal of Pharmaceutics. International Journal of Pharmaceutics. 2021; 595: 120245.).
[0004] Selective laser sintering (SLS) is one of the most popular additive manufacturing processes for producing three-dimensional (3D) objects layer by layer. The process applies layers of powdered material sequentially on top of each other, where the layers are sintered or coalesced together using a laser according to the computer-aided drawing (CAD) geometry of the part.
[0005] SLS is a powder bed based additive manufacturing technology that produces complex three-dimensional parts. In SLS, a rasterized laser is used to scan across a bed of polymer powder, sintering it in a layered manner to form a solid shape. As the laser beam scans the powder, the powder melts due to the increase in temperature, and layer by layer, the final part approaches full density and should produce the properties of the bulk material (i.e., polymer). By controlling the energy input, it is possible to control the density of the sintered material and achieve parts ranging from highly porous to almost fully dense. In theory, every thermoplastic polymer that can be converted into powder form can be processed by this technology, but the reality is that each material behaves differently during melting, coalescence, and consolidation, often with unpredictable behavior, and often requires unique SLS processing parameters. For example, the bed temperature and laser energy input can be selected based on the thermal profile of the polymer and its processing window for energy absorption. Laser parameters can also be selected based on the particle size and shape of the powder.
[0006] There are different types of polymer particles that are commonly used in the SLS process. Semi-crystalline resins such as polyamides including PA12, PA11 and PA6, polylactic acid (PLA), polyetheretherketone (PEEK), polyethylene (PE), polypropylene (PP), etc. are used. The most commonly used polymer powder is polyamide PA12. The common name for polyamide is nylon. For example, polyamide PA12 is also called nylon 12, and polyamide PA6 is also called nylon 6. The laminated structure is formed by sintering the polymer particles together according to the CAD geometry file of the part with a laser above the melting point of the polymer.
[0007] There is currently little or no experience with the use of poloxamers as pharmaceutical excipients in selective laser sintering. So far, the suitability of different poloxamer grades is unknown.
[0008] There is a need for suitable polymers as pharmaceutical excipients having improved properties for selective laser sintering processes. Specifically, laser sintering of polymers should produce pharmaceutical dosage forms in which the API is dispersed in the polymer to form an amorphous solid dispersion. Polymers for this purpose should show improved amorphization of the API and / or beneficial API release. Furthermore, there is a need for polymers that stabilize the API or that can be beneficially used in SLS processes to prevent API degradation. Summary of the invention
[0009] Surprisingly, it has been found that certain poloxamers can be beneficially used in a process of selective laser sintering of sintered powders to form pharmaceutical dosage forms.Poloxamers having a melting point of 20°C or higher are particularly suitable for selective laser sintering.
[0010] Unexpectedly, it was shown that low process temperatures are required to successfully make amorphous solid dispersions using the poloxamers of the present invention. Low temperatures have several advantages over alternative polymers, such as reusability of the poloxamers after printing cycles, increased printing speeds, applicability of the method to a wider range of SLS printers, and reduced energy required for printing. Certain poloxamers show surprisingly fast API release.
[0011] Furthermore, there are optimal ranges of melting point (Tm), molecular weight (MW) and weight percentage of ethylene oxide (EO) chains (wt EO %) which result in a pharmaceutical dosage form having the beneficial properties as mentioned above.
[0012] In a further embodiment of the invention, the poloxamer has a melting point of 20°C to 60°C and / or an average molecular weight of 3000 Da or more and / or a weight percentage of ethylene oxide chains of 50% to 90%. In another embodiment, the poloxamer is poloxamer P188 or P407.
[0013] In a further embodiment of the invention, the poloxamer has a melting point of 40 to 55°C and / or an average molecular weight of 7000 to 12000 Da and / or a weight percentage of ethylene oxide chains of 75 to 85%. In another embodiment, the poloxamer is poloxamer P188.
[0014] In another aspect, the present invention provides a process for producing a pharmaceutical dosage form by selective laser sintering of a sintered powder, comprising the steps of:
[0015] (a) providing a sintered powder comprising at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20° C. or higher, and
[0016] (b) operating a selective laser sintering apparatus which selectively fuses layers of sintered powder to produce a pharmaceutical dosage form.
[0017] A further aspect of the invention relates to a sintering powder for selective laser sintering comprising at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20° C. or higher.
[0018] A further aspect of the invention relates to a pharmaceutical dosage form obtainable by a process as mentioned above, in particular a pharmaceutical dosage form produced by selective laser sintering of a sintered powder comprising at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20° C. or more. DETAILED DESCRIPTION
[0019] One embodiment of the present invention is the use of a poloxamer in a process for selective laser sintering of a sintered powder to form a pharmaceutical dosage form, wherein the sintered powder comprises at least one active pharmaceutical ingredient and a poloxamer.
[0020] According to the present invention, selective laser sintering is a process in which a powder bed filled with a powder mixture containing a polymer is sintered and / or melted using a laser beam by scanning the laser according to a cross-section of a digital model. A polymer version of the digital model is produced in a layer-by-layer manner by laser scanning successive layers of the powder mixture.
[0021] The process will require a selective laser sintering printer equipped with a laser source and a galvanometer system for scanning the laser across the surface of the powder bed or alternatively an xy motion system in which the actual laser source is moved to scan the powder bed. The printer must also provide a powder application system to spread the powder in layers and some heating capability to heat the surface of the build chamber and powder bed.
[0022] According to the present invention, the powder mixture used is prepared by mixing poloxamer powder, excipients and API. (Excipients: pigment, colloidal silicon dioxide). The poloxamer powder is first sieved through a 300 micron sieve, and the material passing through the sieve is mixed with the excipients and API, and mixed in a turbula mixer for 30 minutes. The resulting mixture is then sieved through a 300 micron sieve, and the material passing through the sieve is loaded into the printer.
[0023] After loading the mixture, the printer is preheated to a set temperature below the Tg of the poloxamer and the printing process is started. During the printing process, parameters such as chamber and print bed temperature are set to suitable values obtained through experimental studies to provide printed tablets with desired properties with respect to mechanical and morphological properties. Other parameters that affect the process are the laser energy input and the layer height of each applied layer. Depending on which type of printer is used, the laser energy input can be controlled in a variety of ways, usually via adjusting the laser scanning speed, the hatching space (the distance between the scanned laser lines) or by adjusting the energy output of the laser.
[0024] Once the printing process is complete, the printed tablet is allowed to slowly cool in the printer and then removed from the surrounding unsintered powder and cleaned.
[0025] Poloxamers are amphiphilic polymers with two hydrophilic blocks and a central hydrophobic block. Poloxamers are polyethylene glycol (PEG) / polypropylene glycol (PPG) triblock copolymers whereby one PPG block is flanked on both sides by PEG blocks. The polyethylene glycol (PEG) portion is also commonly referred to as a polyethylene oxide (PEO) portion. The polypropylene glycol (PPG) portion is also commonly referred to as a polypropylene oxide (PPO) portion.
[0026] Poloxamer grades are usually named with the letter P (for poloxamer) followed by three numbers, which are officially used by USP and EP. It describes the composition of the polymer as follows: the first two numbers multiplied by 100 indicate the molecular weight of the PO block, and the last number multiplied by 10 provides the percentage of EO in %.
[0027] Poloxamer P188 consists on average of 80% EO, while the remaining 20% PO constitutes 1800 g / mol. Poloxamer P407 is a poloxamer with an average polyoxypropylene molecular weight of 4000 g / mol and a polyoxyethylene content of 70%.
[0028] Poloxamers have the general formula (I)
[0029]
[0030] For different poloxamers, the number of x (PEO), y (PPO chain) and z (PEO) changes in a wide range, depending on the type of poloxamer. For poloxamer P188, the PPO chain contains an average number of units in the range of 25 to 30, and each PEO is on average composed of 75 to 85 EO units, with a molecular weight of 7680Da to 9510Da in the range. For poloxamer P407, the PPO chain contains an average number of units of 56, and each PEO is on average composed of approximately 101 EO units, with a molecular weight of 9840Da to 14600Da in the range.
[0031] Poloxamer 407 (a=101, b=56), has a molecular weight ranging from 9840 Da to 14600 Da.
[0032] Table 1 shows the types of poloxamers for which monographs are written in the European Pharmacopoeia (Ph. Eur.) and the United States Pharmacopoeia (USP).
[0033] Table 1
[0034]
[0035] Table 2 shows the melting point, molecular weight and weight percentage of ethylene oxide chains (weight EO%) of the most common poloxamers as published in Russo, Villa. Poloxamer Hydrogels for Biomedical Applications. Pharmaceutics. 2019; 11:671.
[0036] Table 2
[0037]
[0038]
[0039] Some poloxamers are commercially available in different ratios of EO and PO units and in different forms such as liquids, pastes and waxy solids, e.g. (Croda International PLC), (BASF SE), (BASF SE changed its name to and ) or Poloxamer 188 EXPERT.
[0040] Alternatively, poloxamers can be prepared from raw materials according to methods known in the art (see, eg, US Pat. Nos. 3,579,465 and 3,740,421).
[0041] Further information on poloxamers can be found in Hagers Handbuch der Pharmazeutischen Praxis, Volume 9 “Stoffe PZ”, 1994, pages 282 to 284 or in Russo, Villa. Poloxamer Hydrogels for Biomedical Applications. Pharmaceutics. 10 2019; 11:671.
[0042] It is of interest to use the specific poloxamer grades according to the invention for formulating solid oral pharmaceutical dosage forms with immediate, immediate or prolonged release of the API. Immediate release or immediate release is preferred.
[0043] The poloxamer according to the present invention has a melting point of 20° C. or higher.
[0044] In a further embodiment, the poloxamer according to the invention has a melting point of 20°C to 60°C, 30°C to 60°C, 40°C to 60°C or 50°C to 60°C. In a further embodiment, the poloxamer according to the invention has an average molecular weight of 3000Da or more, 4000Da to 15000Da or 7000Da to 13000Da. In a further embodiment, the poloxamer according to the invention has a weight percentage of ethylene oxide chains of 50% to 90% or 70% to 85%. In another embodiment, the poloxamer is poloxamer P188 or P407.
[0045] In a further embodiment, the poloxamer according to the present invention has a melting point of 20°C to 60°C, an average molecular weight of 3000 Da or more and a weight percentage of ethylene oxide chains of 50% to 90%.
[0046] In a further embodiment, the poloxamer according to the invention has a melting point of 30 to 60° C., an average molecular weight of 4000 to 15000 Da and a weight percentage of ethylene oxide chains of 70 to 85%.
[0047] In a further embodiment, the poloxamer according to the invention has a melting point of 50 to 60° C., an average molecular weight of 7000 to 13000 Da and a weight percentage of ethylene oxide chains of 70 to 85%.
[0048] In a further embodiment, the poloxamer according to the invention has a melting point of 20°C to 55°C, 30°C to 55°C, 40°C to 55°C or 50°C to 55°C. In a further embodiment, the poloxamer according to the invention has an average molecular weight of 4000Da to 12000Da or 7000Da to 12000Da. In a further embodiment, the poloxamer according to the invention has a weight percentage of ethylene oxide chains of 75% to 85% or 80% to 85%. In another embodiment, the poloxamer is poloxamer P188.
[0049] In a further embodiment, the poloxamer according to the invention has a melting point of 20°C to 55°C, an average molecular weight of 4000 Da to 12000 Da and a weight percentage of ethylene oxide chains of 75% to 85%.
[0050] In a further embodiment, the poloxamer according to the invention has a melting point of 40 to 55°C, an average molecular weight of 7000 to 12000 Da and a weight percentage of ethylene oxide chains of 75 to 85%.
[0051] In a further embodiment, the poloxamer according to the invention has a melting point of 50 to 55° C., an average molecular weight of 7000 to 12000 Da and a weight percentage of ethylene oxide chains of 80 to 85%.
[0052] In a further embodiment, the poloxamer according to the invention has a melting point of about 52°C and / or an average molecular weight of 7680 to 9510 Da and / or a weight percentage of ethylene oxide chains of 80% to 85%. In a further embodiment of the invention, the poloxamer is poloxamer P188.
[0053] In a further embodiment, the poloxamer according to the invention has a melting point of about 56°C and / or an average molecular weight of 9840 to 14600 Da and / or a weight percentage of ethylene oxide chains of 70% to 75%. In a further embodiment of the invention, the poloxamer is poloxamer P407.
[0054] The above-mentioned embodiment poloxamers, poloxamer specifications and poloxamer grades are also applicable to the use of poloxamer in the following: a selective laser sintering process of sintering powder, a process for producing a pharmaceutical dosage form by selective laser sintering of sintering powder, a sintering powder for selective laser sintering and a pharmaceutical dosage form produced by selective laser sintering of sintering powder.
[0055] A further embodiment of the present invention is a sintering powder for selective laser sintering, comprising at least one active pharmaceutical ingredient and at least one poloxamer according to the invention.
[0056] For the avoidance of doubt, sintered powders according to the present invention include sintered powders having any of the poloxamer, poloxamer specifications or poloxamer grades as defined above.
[0057] In other embodiments of the present invention, sintered powders and pharmaceutical dosage forms may include additional pharmaceutically acceptable excipients. Pharmaceutically acceptable excipients include flow control agents such as silicon dioxide, fillers, plasticizers, surfactants, light absorbing materials such as ruby red or Candurin pigments and other suitable components well known to those skilled in the art.
[0058] Depending on the wavelength of the light emitted by the laser, a light absorbing material (pigment) may be needed that absorbs light at the emission wavelength. These light absorbing materials may contain transition metals for absorption at about 450nm or carbon for a wider range covering the visible and near infrared ranges. Light absorption is the process by which light is absorbed and converted into energy. When light is absorbed, heat is generated. Selective absorption of light by a particular material therefore occurs because the frequency of the light wave matches the frequency at which the electrons in the atoms of that material vibrate.
[0059] Light absorbing materials are all materials suitable for the SLS method described above and are known to those skilled in the art. Preferably, light absorbing materials that have been proven to work under 445 nm laser irradiation are used, such as Candurin NXT, Ruby Red, Candurin Gold Sheen, aluminum lake, activated carbon (also working at 808 nm) or iron oxide (Fe2O3). More preferably, Ruby Red is used.
[0060] CO2 lasers emitting at about 10 microns do not usually require the addition of light absorbing materials because CH bonds absorb energy well at this wavelength and this type of bond can be found in most polymers.
[0061] For the avoidance of doubt, flow control agents, plasticizers, surfactants or other suitable components are not required for the beneficial properties according to the present invention, such as stabilizing the amorphous form of the API. However, those components may be used for other purposes, such as for optimizing the manufacturing process of the pharmaceutical composition or oral dosage form according to the present invention.
[0062] Furthermore, the pharmaceutical composition according to the present invention may comprise additional pharmaceutically acceptable hydrophilic or lipophilic polymers.
[0063] In a preferred embodiment, the sintered powder further comprises a light absorbing material.
[0064] As used herein, the phrase "pharmaceutically acceptable" refers to all excipients, polymers, compounds, solvents, dispersion media, flow control agents, carriers, coatings, active agents, isotonic agents, absorption delaying agents, etc., which do not substantially produce allergic or similar adverse reactions when administered to humans. The use of such substances in pharmaceutical compositions is well known in the art.
[0065] In a preferred embodiment, the particle size of the sintered powder has a D50 of 200 μm or less. Preferably, the particle size (D50) of the sintered powder is 20 μm to 200 μm, 20 μm to 150 μm, or 20 μm to 100 μm.
[0066] In a preferred embodiment, the particle size of the poloxamer has a D50 of 200 μm or less. Preferably, the particle size (D50) of the poloxamer is 20 μm to 200 μm, 20 μm to 150 μm or 20 μm to 100 μm.
[0067] A further embodiment of the invention is a process for producing a pharmaceutical dosage form by selective laser sintering of sintered powders, comprising the following steps:
[0068] (a) providing a sintered powder comprising at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20° C. or higher, and
[0069] (b) operating a selective laser sintering apparatus which selectively fuses layers of sintered powder to produce a pharmaceutical dosage form.
[0070] For the avoidance of doubt, the process according to the present invention comprises selective laser sintering with any of the poloxamers, poloxamer specifications or poloxamer grades as defined above.
[0071] A further embodiment of the present invention is a pharmaceutical dosage form obtainable by a process for producing a pharmaceutical dosage form by selective laser sintering of a sintered powder as described above.
[0072] In a further embodiment, the pharmaceutical dosage form is produced by selective laser sintering of a sintered powder, wherein the sintered powder comprises at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20° C. or higher.
[0073] For the avoidance of doubt, pharmaceutical dosage forms according to the present invention include pharmaceutical dosage forms having any of the poloxamers, poloxamer strengths or poloxamer grades as defined above.
[0074] API is a bioactive agent. API can be a small molecule in the form of a weak base, weak acid or neutral molecule, and can be in the form of one or more pharmaceutically acceptable salts, esters, derivatives, analogs, prodrugs and solvates thereof. Sintered powders and pharmaceutical dosage forms can contain more than one API. In one embodiment, API is a poorly soluble or lipophilic API.
[0075] As used herein, the terms "poorly soluble API", "poorly water-soluble API" and "lipophilic API" refer to APIs having such solubility that the highest therapeutic dose of the specific API to be administered to an individual cannot be dissolved in 250 ml of an aqueous medium with a pH range of 1 to 8, which follows the definition of low solubility according to Biopharmaceutics Classification System (BCS) Classes 2 and 4. Poorly soluble APIs with weakly basic or weakly acidic characteristics have pH-dependent solubility characteristics and can have a wide range of solubility in the aqueous environment of the gastrointestinal tract. APIs falling into BCS Classes 2 or 4, respectively, are well known to those skilled in the art.
[0076] In one embodiment, the API is a weakly basic API. As used herein, the term "weakly basic API" refers to a basic active pharmaceutical ingredient (API), wherein the basic API is not completely ionized in water.
[0077] At least one active pharmaceutical ingredient (API) according to the present invention may be dispersed in a poloxamer to form an amorphous solid dispersion.
[0078] Another embodiment of the present invention is the use of a poloxamer as described above in a process for selective laser sintering of sintered powders to form a pharmaceutical dosage form, wherein an amorphous solid dispersion of at least one active pharmaceutical ingredient in the poloxamer is formed.
[0079] As used herein, the term "amorphous solid dispersion" is a dispersion of at least one amorphous API in a polymer matrix. Preferably, the amorphous API is distributed in a molecularly dispersed state within the polymer matrix. In this case, the solid dispersion is a solid solution. Upon dissolution, a formulation comprising an amorphous solid dispersion can achieve a higher solubility in an aqueous medium than a crystalline API.
[0080] The API contained in the pharmaceutical dosage form of the present invention has an amount sufficient to be therapeutically effective. For a given API, the therapeutically effective amount is generally known or readily available to those skilled in the art. Typically, the API can be present in the pharmaceutical dosage form in a weight ratio of API to poloxamer of 0.1:99.1 to 60:40, preferably 1:99 to 50:50, more preferably 5:95 to 40:60 and most preferably 10:90 to 30:70.
[0081] It was found that poloxamers can be beneficially used in a process of selective laser sintering of sintered powders to form pharmaceutical dosage forms.
[0082] The selective laser sintering process requires surprisingly low process temperatures. Example 1 surprisingly shows that the inventive SLS printing technology with the above mentioned poloxamers can successfully produce amorphous solid dispersions with a print bed temperature of about 50°C and a chamber temperature of room temperature. It was not expected that pharmaceutical dosage forms with an amorphous API stabilized in a polymer matrix could be produced with the SLS technology at this range of temperatures.
[0083] Cryogenics offers a number of advantages over alternative SLS processes with different polymers:
[0084] 1. Due to the low temperature, the sintered powder remaining on the print bed after a printing cycle can be reused several times without any degradation in print quality. This has not been seen with any other polymer.
[0085] 2. Low printing temperatures make it possible to print parts without heating the print chamber, which allows the use of simpler and lower-cost printers.
[0086] 3. Low printing temperatures make it possible to use fast printing speeds and thereby reduce production time. In addition, thermal stress of the API decreases with higher printing speeds.
[0087] 4. The low printing temperature of the polymer reduces the amount of energy necessary for the printing process. Therefore, the SLS printing process with the above-mentioned poloxamer has better environmental sustainability.
[0088] Although the process was carried out at a temperature well below the melting point of the model drug substance, the crystalline drug was successfully converted into its amorphous form and an amorphous solid dispersion could be manufactured.
[0089] Compared with other poloxamers, some poloxamers show surprisingly fast drug release. Specifically, compared with poloxamers falling outside the specifications, poloxamers with a melting point of 40°C to 55°C, preferably 50°C to 55°C and / or an average molecular weight of 7000Da to 12000Da, preferably 7000Da to 9000Da and / or a weight percentage of ethylene oxide chains of 75% to 85%, preferably 75% to 80% show fast API dissolution of the pharmaceutical dosage form. In another embodiment, poloxamer P188 shows quite fast API dissolution. Surprisingly, fast drug dissolution is the result of a combination of the process (SLS technology) used to produce the pharmaceutical dosage form and the selection of the poloxamer. This has been confirmed by using different 3D printing technologies with the same poloxamer grade (which did not cause improvements in the dissolution of the API).
[0090] Certain poloxamers show surprisingly improved amorphization of APIs compared to other poloxamers. In particular, poloxamers having a melting point of 40°C to 55°C, preferably 50°C to 55°C and / or an average molecular weight of 7000Da to 12000Da, preferably 7000Da to 9000Da and / or a weight percentage of ethylene oxide chains of 75% to 85%, preferably 75% to 80%, show fast API dissolution from pharmaceutical dosage forms compared to poloxamers falling outside of the specification. In another embodiment, poloxamer P188 shows improved amorphization of APIs compared to other poloxamers.
[0091] Furthermore, the poloxamer having the melting point, molecular weight and / or weight percentage of ethylene oxide chains identified above ensures and stabilizes the release and supersaturation of the API, in particular the poorly soluble API, in the aqueous medium, thereby preventing crystallization and phase separation. Since the low water solubility of the API in pharmaceutical preparations is generally accompanied by a low bioavailability after its administration, the composition according to the invention also helps to improve the bioavailability of poorly water-soluble APIs, and in particular the bioavailability of weakly basic APIs.
[0092] As used herein, "bioavailability" is a term referring to the extent to which an API becomes available to target tissues after administration to a patient's body.
[0093] After dissolving the pharmaceutical dosage form of the present invention, improved supersaturation is observed and the API is better kept in solution. In addition, the API can be better incorporated into the poloxamer matrix during the sintering process.
[0094] After entering the gastrointestinal tract, the pharmaceutical dosage form swells and disintegrates in the aqueous environment of the gastrointestinal fluid, thereby releasing the API. Although the salt form of the weakly basic API can show an increased initial aqueous solution concentration in acidic gastric juice, the weakly basic API is quickly converted into a free base form in a more neutral intestinal juice, and the API in the free base form has a significantly lower equilibrium concentration in the intestinal juice. Compared with the poloxamer falling outside the mentioned specifications, the poloxamer according to the present invention maintains an increased concentration of the API in a model solution simulating acidic and neutral gastrointestinal solutions. Therefore, the pharmaceutical dosage form according to the present invention has the potential for providing an enhanced bioavailability of an API with poor solubility. The solubility-improved form of the API in the presence of the poloxamer according to the present invention provides such a concentration of the API in gastric juice or simulated gastric juice, which is greater than the concentration of the API provided in the presence of the poloxamer falling outside the mentioned specifications.
[0095] Example
[0096] Example 1: SLS printing
[0097] Preparation of powder formulations
[0098] API loaded powder formulations were prepared according to Table 3. All powder mixtures were sieved using a 315 μm stainless steel test sieve (VWR International AB, Sweden) and mixed using a Turbula oscillator (Turbula T2F oscillator, Glen Mills, Inc., Clifton, NJ, US) for 15 minutes. Candurin ruby red and colloidal silicon dioxide (Aerosil) were added to the formulations to enhance the laser energy absorption of the powder and improve the flowability of the powder during the layer application process, respectively. As poloxamer, P188 (Poloxamer 188 EXPERT, Merck) and P407 (Merck). Formulations were prepared in batches (approximately 1500 mL) large enough to partially fill the build volume (100x100x100 mm) of a Sintratec Kit SLS 3D printer (Sintratec, Brugg, Switzerland).
[0099] Table 3. Composition of the prepared powder formulations
[0100]
[0101] Selective Laser Sintering 3D Printing of Dosage Forms
[0102] Creating and designing tablet templates in Solidworks 2019SP05 ( Figure 1 ), and the obtained standard triangle language file (STL-file) was then prepared for printing in the Sintratec software using the process parameters presented in Table 4. The energy density was calculated according to the following equation:
[0103]
[0104] P - laser power (2.3 W); HS - hatch spacing (0.05 mm); V - scanning speed (mm / s); α - absorption coefficient of powder (the coefficient should be measured / calculated for each powder type with respect to absorption at 445 nm).
[0105] The 3D printing process is further implemented as follows: the prepared powder formulation (Table 3) is placed and loaded into the powder reservoir platform (100x100x100mm) of the SLS 3D printer. Thereafter, a thin layer of the formulation is spread onto the build platform, after which the powder bed is slowly heated to the temperature specified in Table 4. The sintering process is implemented layer by layer using a 2.3W laser diode (λ=445nm) according to the model given in the STL-file. With the build platform level, a total of 36 tablets are printed per batch using the layer height specified in Table 4. When printing different batches, a specific value of the laser scanning speed is selected. At the end of the printing process, the completed batch is collected from the build platform by sieving. The tablets are additionally dedusted using pressurized air to remove excess powder and stored in a sealed container for further analysis.
[0106] Figure 1 Schematic diagram and 3D model showing a tablet (4x9.5 mm).
[0107] The print speed, print bed temperature, and hatch spacing are adjusted so that the correct amount of energy is applied to the material in order to account for different materials with different melting temperatures and different particle sizes, which require different temperatures to sinter properly.
[0108] Table 4. Process parameters for various formulations
[0109]
[0110] Characterization of powder formulations and 3D printed dosage forms
[0111] Using Cu-Kα1,2 Powder X-ray diffraction (PXRD) diffractograms of the original and heat-treated powder formulations as well as the printed dosage forms were collected on a Bruker D8 Advance TwinTwin diffractometer (Bremen, Germany). The instrument was operated at 40 mA and 40 kV, using a step size of 0.02° and a data collection time of 1 h.
[0112] Fig. 9 and 10 Diffraction patterns of an indomethacin-loaded tablet and a ketoconazole-loaded tablet are shown. The X-ray diffraction patterns confirm the amorphization of the API within the 3D printed tablet matrix.
[0113] Use 10℃min -1 Differential scanning calorimetry (DSC) thermograms were obtained on a Mettler Toledo DSC 3+ (Schwerzenbach, Switzerland) with heating and cooling rates of 100 °C and using nitrogen as the purge gas. Repeated heating-cooling measurements were performed from -40 °C to 200 °C and from 200 °C to 10 °C in the first cycle and from 10 °C to 200 °C in the subsequent cycles. The size (n = 10) and weight (n = 30) of the printed tablets were checked using a digital caliper and an analytical balance (Mettler Toledo XS 64 analytical balance, Schwerzenbach, Switzerland).
[0114] Figures 2 to 8 The DSC thermograms are shown for pure indomethacin ( Figure 2 ), pure polymer / placebo tablets without API ( Figure 3 ), P188 loaded with indomethacin ( Figure 4 ), P407 loaded with indomethacin ( Figure 5 ), P188 and P407 loaded with ketoconazole ( Figure 6 ), P188 loaded with ketoconazole ( Figure 7 ) and ketoconazole-loaded P407 ( Figure 8 ). The batch numbers (Table 3) are indicated as # numbers in the figure. The thermogram of indomethacin shows a clear melting peak of the API. It can be shown that the melting peak of indomethacin is no longer available in the 3D printed tablets, which indicates complete amorphization of the API.
[0115] The friability test was performed according to the European Pharmacopoeia (ed. 10.0) on tablets of about 6.5 g using a Pharmatest PTF E friability tester (Hainberg, Germany) at 25 rpm for 100 revolutions. The tablets were carefully weighed before and after the measurement and the total weight loss of the tablets (ie friability) was calculated.
[0116] Dissolution data were performed on a Sotax AT7 dissolution tester via HPLC from Agilent 1260infinity II. The mobile phase contained a mixture of 1000 ml acetonitrile + 1000 ml buffer USP (0,01 M NaH2PO*H2O1,38 g / L + 0,01 MNa2HPO4 1,41 g / L), both mixed 1:1 and sonicated for 15 minutes. A 5-point calibration of appropriate indomethacin was prepared in the mobile phase.
[0117] Dissolution was performed with n=3 tablets in 500 ml SGF_SP, paddle, 50 rpm for 3 hours with sampling points (15, 30, 60, 90, 120 and 180 minutes). 2 ml of sample was filtered through a 0,45 μm PTFE syringe filter and directly measured by HPLC on a LC-18, 30 cm x 4 mm, 5 μm column at 254 nm, 10 μl injection volume and 1 ml / min flow rate and 5 minutes run time.
[0118] Hardness testing was performed on 10 cylindrical tablets (10 mm in diameter) from each batch in order to define the tablet hardness (given in Newtons (N)). A Pharmatest PTB 311E tablet hardness testing instrument (Hainberg, Germany) was used.
[0119] For cylindrical shapes, the splitting tensile strength is calculated according to the following equation:
[0120]
[0121] (P-maximum applied load (N), L-length (m), D-diameter)
[0122] The friability test was performed according to EP 5.0, paragraph 2.9.7 - Friability of uncoated tablets.
[0123] For tablets weighing up to 0.65 g each, take a sample of 20 tablets; for tablets weighing more than 0.65 g each, take ten tablets. Place the tablets on a No. 1000 sieve and remove any loose dust with the aid of air pressure or a soft brush. Accurately weigh the tablet sample and place the tablet in a drum. Rotate the drum 100 times and remove the tablets. Remove any loose dust from the tablets as before. If no tablets are cracked, split or broken, weigh the tablets to the nearest milligram.
[0124] Table 5. Characterization of 3D printed dosage forms
[0125]
Claims
1. Use of a poloxamer in a process for selective laser sintering of a sintered powder to form a pharmaceutical dosage form, wherein the sintered powder comprises at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20° C. or higher.
2. Use according to claim 1, wherein the at least one poloxamer has a melting point of 40°C to 60°C.
3. The use according to claim 1 or 2, wherein the at least one poloxamer has an average molecular weight of 3000 Da or more.
4. Use according to any one of claims 1 to 3, wherein the at least one poloxamer has a weight percentage of ethylene oxide chains of 50% to 90%.
5. Use according to any one of claims 1 to 4, wherein the at least one poloxamer is poloxamer P188 or P407.
6. Use according to any one of claims 1 to 5, wherein the sintered powder further comprises at least one light absorbing material.
7. A process for producing a pharmaceutical dosage form by selective laser sintering of a sintered powder, comprising the following steps: (a) providing a sintered powder comprising at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20° C. or higher, and (b) operating a selective laser sintering apparatus which selectively fuses layers of sintered powder to produce a pharmaceutical dosage form.
8. The process according to claim 7, wherein the pharmaceutical dosage form is an amorphous solid dispersion of the at least one active pharmaceutical ingredient in the at least one poloxamer.
9. The process according to claim 7 or 8, wherein the at least one poloxamer is poloxamer P188 or P407.
10. The process according to any one of claims 7 to 9, wherein the process temperature is below the melting point of the at least one poloxamer.
11. The process according to any one of claims 7 to 10, wherein the particle size of the sintered powder has a D50 of 200 μm or less.
12. The process according to any one of claims 7 to 11, wherein the sintered powder further comprises at least one light absorbing material.
13. A sintering powder for selective laser sintering, comprising at least one active pharmaceutical ingredient and at least one poloxamer having a melting point of 20°C or higher.
14. The sintered powder according to claim 13, further comprising at least one light absorbing material.
15. A pharmaceutical dosage form obtainable by a process according to any one of claims 7 to 12.
Citation Information
Patent Citations
Aqueous GELS of polyoxyethylated polyoxypropylene glycol adducts of ethylene diamine
US3579465A
Polyoxyethylene-polyoxypropylene aqueous gels
US3740421A